Diversity of Ant Spesies (Hymenoptera: Formiciidae) in Refugia Plants Combination on Ratoon Sugarcane - Mawaddah, Rabbiana; Rahardjo, Bambang Tri; Mudjiono, Gatot (Research Journal of Life Science, 2022)
This research aims to examine the effects of several refugia plant treatments on the diversity and number of ants in the ratoon sugarcane system. The diversity and abundance of ants in the plantation's surrounding habitats can fluctuate. Three combinations of flowering plants were used in the study: Turnera subulata Sm (Malpighiales: Passifloraceae), Cosmos sulphureus (Asteraceae: Asteraceae), and Zinnia elegans Jaqc (Asterales: Asteraceae). Ant samples were collected using yellow sticky traps and traps and yellow pan traps. R. software was used to examine all of the data. 4 subfamilies, 14 genera, and 25 species: Diacamma sp., Technomyrmex sp., Camponotus sp.1., Iridiomyrmex sp., Delichoderus sp., Leptogenys sp.; Odontomachus sp., Polyrachis sp., Pheidole sp., Tetramorium sp., Monomorium sp., Crematogaster sp., Oecophylla smaragdina was identified from the report's results, this included 1-86 individuals. Tetramorium sp. and Odonthomachus sp. were the most common ants found at the study site. Even before compared to the other treatments, the combination of refugia and Z. elegans, C. sulphureus, T. subulata treatment used to have a significant impact on the presence of ants, increasing the population by 21%. This study discovered that combining refugia could increase ant diversity in ratoon sugarcane. The diversity index value for all treatments was almost the same, in the range of 2.-9-2.82, indicating that the main composition of refugia was moderately diverse.